Self-experience in dementia - Summa, Michela; Fuchs, Thomas (Rivista Internazionale di Filosofia e Psicologia, 2015)
This paper develops a phenomenological analysis of the disturbances of self-experience in dementia. After considering the lack of conceptual clarity regarding the notions of self and person in current research on dementia, we develop a phenomenological theory of the structure of self-experience in the first section. Within this complex structure, we distinguish between the basic level of pre-reflective self-awareness, the episodic sense of self, and the narrative constitution of the self. In the second section, we focus on dementia and argue that, despite the impairment of narrative self-understanding, more basic moments of self-experience are preserved. In accordance with the theory developed in the first part, we argue that, at least until the final stages of the illness, these self-experience in dementia goes beyond the pure minimal self, and rather entail forms of self-reference and an episodic sense of self.Keywords: Narrative Self; Episodic Self; Minimal Self; Dementia; Self-disturbances; Phenomenological Psychopathology. L’esperienza del sé nella demenzaRiassunto: Questo articolo sviluppa un’analisi fenomenologica dei disturbi dell’esperienza del sé nella demenza. Dopo aver considerato l’assenza di una piena chiarezza concettuale circa le nozioni di “sé” e “persona” nella letteratura sulle demenze, la prima parte dell’articolo sviluppa una teoria fenomenologica dell’esperienza del sé. In questa struttura complessa distingueremo il livello dell’esperienza preriflessiva del sé, il senso episodico del sé e la costituzione narrativa del sé. Nella seconda parte ci concentreremo sulla demenza, sostenendo che, malgrado la compromissione dell’esperienza del sé narrativo, restano preservati momenti più elementari dell’esperienza del sé. Coerentemente con la teoria presentata nella prima parte, sosterremo che, quantomeno nelle fasi finali della malattia, questi momenti non si limitano alla dimensione del puro sé minimo, ma implicano forme di auto-riferimento e un senso episodico del sé.Parole chiave: Sè narrativo; Sè episodico; Sé minimo; Demenza; Disturbi del sè; Psicopatologia fenomenologica.